Joint effect of smoking and NQO1 C609T polymorphism on undifferentiated nasopharyngeal carcinoma risk in a North African population. - (:unkn) unknown (My University, 2018)
BACKGROUND:Nasopharyngeal carcinoma (NPC) has a higher incidence in North Africa than in most parts of the world. In addition to environmental factors such as Epstein-Barr virus infection and chemical carcinogen exposure, genetic susceptibility has been reported to play a key role in the development of NPC. NAD(P)H: quinone oxidoreductase 1 is a cytosolic enzyme that protects cells from oxidative damage. A C to T transition at position 609 in the NQO1 gene (OMIM: 125860) has been shown to alter the enzymatic activity of the enzyme and has been associated with increased risk to several cancers. This study investigates for the first time the effect of this polymorphism on NPC susceptibility in a North African population.METHODS:The NQO1 C609T polymorphism was genotyped using PCR-RFLP in 392 NPC cases and 365 controls from Morocco, Algeria, and Tunisia.RESULTS:The allele frequencies and distributions of genotypes did not differ between cases and controls (p > 0.05). When stratifying according to smoking status, we observed two-fold higher NPC risk in ever-smokers carrying the CT or TT genotype. Multiple logistic regression analysis revealed that there was a significant interaction between T allele and smoking status (OR = 1.95, 95% CI = 1.20-3.19; interaction p = 0.007).CONCLUSION:In this North African population, the functional NQO1 polymorphism was associated with a significantly higher risk of NPC among smokers and did not affect the risk among nonsmokers.
Keywords: African Research